2018
DOI: 10.1021/acsomega.8b02230
|View full text |Cite
|
Sign up to set email alerts
|

Transprotein-Electropore Characterization: A Molecular Dynamics Investigation on Human AQP4

Abstract: Electroporation characterization is a topic of intensive interest probed by extensive ongoing research efforts. Usually, these studies are carried out on lipid-bilayer electroporation. Surprisingly, the possibility of water-channel electropore formation across transmembrane proteins themselves, particularly in view of such a promising application, has not yet been elucidated. The present work examines the geometrical and kinetic aspects of electropores and their stability in such a protein milieux (as opposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 63 publications
1
5
1
Order By: Relevance
“…Our conclusions are mainly built on analyses of protein hydration and electrostatic profiles, which can be straightforwardly performed on other membrane proteins. In this regard, a recent MD study on a human aquaporin has revealed the formation of a transient electric-field-induced pore through this protein; unlike the complex pores observed in our simulations, this pore closed within ∼20 ns after turning off the electric field ( 75 , 76 ). In our work, we additionally reported conduction of ions through the central channel pore in the NavMs structure, which was presumably solved in an open state.…”
Section: Discussioncontrasting
confidence: 51%
“…Our conclusions are mainly built on analyses of protein hydration and electrostatic profiles, which can be straightforwardly performed on other membrane proteins. In this regard, a recent MD study on a human aquaporin has revealed the formation of a transient electric-field-induced pore through this protein; unlike the complex pores observed in our simulations, this pore closed within ∼20 ns after turning off the electric field ( 75 , 76 ). In our work, we additionally reported conduction of ions through the central channel pore in the NavMs structure, which was presumably solved in an open state.…”
Section: Discussioncontrasting
confidence: 51%
“…Our conclusions are mainly built on the analyses of protein hydration and electrostatic profiles, which can be straightforwardly performed on other membrane proteins. In this regard, a recent MD study on a human aquaporin has revealed formation of a transient electric-field induced pore through this protein; unlike the complex pores observed in our simulations, this pore closed within about 20 ns after turning off the electric field (71,72). In our work we additionally reported conduction of ions through the central channel pore in the NavMs structure, which was presumably solved in an open state.…”
Section: Discussionsupporting
confidence: 52%
“…Most of the investigations have been performed in silico [22] , where they explored either membrane [23] or protein systems. The effect of the electric field was mostly on the secondary structure, conformation, and orientation of various proteins [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , including cytoskeletal system proteins such as tubulin [43] , [44] , [45] , [46] , [47] and kinesin [48] , even leading to the unfolding of some proteins [49] , [50] , [51] . Most of this work explored electric field effects either in a single protein or membrane-bound proteins systems.…”
Section: Introductionmentioning
confidence: 99%